Object Detection and Tracking in Real Time Video - Kaushik, Rajkumar; Swami, Subhash Chander; Sharma, Dev; Sharma, Dev; Ahluwalia, Peeyush (International Journal of Psychosocial Rehabilitation, 2020)
Object tracking is the process of locating moving objects over time using the camera in video sequences. The objective of object tracking is to associate target objects in consecutive video frames. Object tracking requires the location and shape or features of objects in the video frames. So, object detection and object classification are the preceding steps of object tracking in computer vision applications. To detect or locate the moving object in the frame, Object detection is the first stage in tracking. It is a challenging or difficult task in image processing to track the objects into consecutive frames. Various challenges can arise due to complex object motion, irregular shape of object, occlusion of object to object and object to the scene, and real-time processing requirements. This paper presents the various techniques of object tracking in video sequences.